Characteristics Study and Total Flavonoids Quantification of Kareho Leaves (Callicarpa longifolia Lam) - Nashrul Wathan; Fadlilaturrahmah Fadlilaturrahmah; Saufy Arishandi; Akhmad Rezeki Firdaus (Journal of Pharmascience, 2021)
The Callicarpa longifolia Lam. known as ‘kareho’ is one of the plants used by several Dayak tribes for traditional medicine such as antiacne, swelling, wounds, diarrhea, diabetes, and lowering cholesterol levels. This study has obtained scientific data on the characteristics of dried leaves and determined the flavonoids levels of methanol extract of C. longifolia leaves. Characterization includes both qualitative and quantitative examination on the dried leaves of C. longifolia leaves, while the determination of total flavonoid content was determined by the aluminium chloride method and calculated as quercetin equivalent (QE). The results of characteristics observations obtained organoleptic in the form of powder, dark green, bitter taste and have a distinctive smell. Microscopic test of leaves had an actinositic stomata type, ethanol soluble extract content of 17.50 ± 0.10% and water soluble extract content of 16.53 ± 0.37%. Drying loss 8.16 ± 0.25%, total ash content of 5.52 ± 0.06%, and acid insoluble ash content of 0.07 ± 0.01%. The results of phytochemical screening confirmed the presence of saponins, flavonoids, steroids, tannins, glycosides, and phenols. TLC observasions using 254 nm UV light obtained 6 spots and 7 spots appearance on sulphuric acid. It has total flavonoid levels obtained at 7.995 ± 0.050% w/w QE.